Student’s Creative Thinking Skills Viewed by Adversity Quotient and Mathematics Anxiety in Grade VIII - Wahyuningtyas, Febriana; Suyitno, Hardi; Asikin, Mohammad (Unnes Journal of Mathematics Education Research, 2020)
Creativity, math anxiety, and adversity quotient play a significant role in mathematics. This study aims to describe student’s creative thinking skills viewed by adversity quotient and mathematics anxiety. This research is a descriptive qualitative approach. Subjects in this study were students of SMP N 9 Semarang, and students of SMP N 8 Semarang grade VIII who selected by adversity quotient and mathematics anxiety. Data was collecting by questionnaire, observation, test, and interview. The result showed that (1) creative thinking skills in climber students classified creative (able to satisfy fluency, flexibility, and novelty) and less creative (able to satisfy fluency, and flexibility), (2) creative thinking skills in camper students classified less creative, they were able to satisfy fluency, and flexibility , (3) creative thinking skills in quitter students classified not creative, they were only able to satisfy fluency.